Structural Model Analysis for the Laser Guided Mobile Short-Range Air Defence System - Rimantas BARAUSKAS; Algimantas FEDARAVIČIUS; Karolis JASAS (Problemy Mechatroniki)
This article provides structural model analysis of characteristics of the vehicle movement during the shooting from a laser guided short-range air defence system mounted on it. Every shot causes a recoil, which significantly affects vibration of the vehicle and determines the shortest time duration between each two successive shots. The numerical simulation with MATLAB software enabled us verification of the created structural model and it facilitated the understanding of mechanical phenomena which are the most important for achieving the proper vibrational characteristics of the system. Main modes of the system movements during missile launch and their effect on the launcher and the vehicle were determined.